The impact of production elements responsible on the environmental management system requirements of ISO 14001 - 2004 field study in the North Gas Company - محمد محمد ابراهيم (Journal of Economics and Administrative Sciences, 2016)
Abstract Most of the industrial organization in the world became suffering from the problem of the pollution of the poisonous chemicals things, this urged to depend on the principle of the responsible production, because it has the positive role by dealing with these chemical things and to safe the health of the society, due to the main goal of this study is to restrict the role responsible production in accomplishing the system of the environmental management through an actual study in the northern gas company in Kirkuk province, the topic has acquired a big importance bacause there were a limited number of studies and researches which dealt with this topic in Iraqi and Arabic environment. The reasearcher has looked for including it in his current study through a full framework by using the questionnair technique as a main strategy to collect the information, and data in order to get the result of (spss) and analyzing it by the ready analyzing package, which reflects the actual side of this study and proving the validity of its theories, due to the study has found a group of conclusions the most important one was that there is a relationship of the vestige the correlation between the two variable things in this study, so according to these results, the study has proposed some important one is to develop the system of production in the company which enables the connection between the system of responsible production and the system of the environmental management which the current study has depended on and this will enable it to keep the natural environment forever.